2023
DOI: 10.3389/fonc.2023.1012783
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and outcomes of ramucirumab and docetaxel in patients with metastatic non-small cell lung cancer after disease progression on immune checkpoint inhibitor therapy: Results of a monocentric, retrospective analysis

Abstract: Current first-line standard therapy for metastatic non-small cell lung cancer without driver mutations involves chemotherapy and immunotherapy combination. Prior to the advent of immune checkpoint inhibition, REVEL, a randomized phase III trial demonstrated improved progression-free and overall survival with ramucirumab and docetaxel (ram+doc) in patients who failed platinum-based first-line therapy. Long-term outcomes related to second-line ramucirumab and docetaxel after first-line immunotherapy exposure rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that the efficacy of DTX 10 , 11 , 12 , 13 , 14 and DTX + RAM 8 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 therapies may be enhanced in patients who were previously treated with ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the efficacy of DTX 10 , 11 , 12 , 13 , 14 and DTX + RAM 8 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 therapies may be enhanced in patients who were previously treated with ICIs.…”
Section: Discussionmentioning
confidence: 99%